Elmo's world. The street we live on! - Diego, Ken.; Clash, Kevin; DiNapoli, Victor; Nelson, Jerry, 1934-2012; Oz, Frank; Spinney, Caroll; Whitmire, Steve, 1959-; Jacobson, Eric.; Golden, Bob.; Lawrence, Stephen; Siegal, Donald Alan, 1950-2004.; Sesame Workshop; et al. (New York : Sony Wonder, 2004)
The entire cast of Sesame Street is part of the 35th Anniversary Special celebration. Join in this walk down Sesame Street with Elmo and sing along with a brand new song that celebrates the Street everyone knows and loves!
At head of title: 35th anniversary special!
Art directors, Alan J. Compton, Valerie Green ; music, Bob Golden, Stephen Lawrence, Donald Alan Siegel.
Kevin Clash, Jerry Nelson, Frank Oz, Carroll Spinney, Steve Whitmire, Eric Jacobson, Jim Henson, Fran Brill.
Not rated.
DVD, full screen; Dolby Digital.
Closed-captioned.
Keywords: Elmo (Fictitious character : Henson) -- Juvenile drama; Big Bird (Fictitious character) -- Juvenile drama; Grover (Fictitious character : Henson) -- Juvenile drama; Bert (Fictitious character : Henson) -- Juvenile drama; Ernie (Fictitious character : Henson) -- Juvenile drama; Puppet television programs; Children's television programs; Video recordings for the hearing impaired